Innovations in legal education - Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The discussion concerning problems of implementation of the Law of Ukraine «On higher education», integration of modern legislation on education in the European educational space, legal education modernization, the usage of interactive technologies and new methodological approaches to the teaching of legal disciplines, the influence of scientific researches’ level on the quality of educational process is summarized. After adoption of the Law of Ukraine "On Higher Education", its main provisions, innovations, changes that it will bring to the education system of Ukraine, are actively discussed. Nowadays one of the most important tasks of a perspective education system is to retrain specialists, including scientific personnel, who are able to develop and use information technologies of teaching. It’s concluded in the article that All Ukrainian conference "Innovations in legal education" devoted to the Day of Science directs scientific and educational activities, integrates views of students, graduate students, young scientists, experienced teaching staff, practitioners, for the isolation priorities for a faster enforcement of the new Law of Ukraine "On Higher Education", better understanding of education reforms, realization of their purpose and implementation mechanism. The author also points out that an important result of this scientific event is a desire of each of us to change, follow the changes of the time, support the innovations and reach all the goals. It’s emphasized that a high level of education development, scientific achievements and innovations are the guarantee of freedom and democracy in our country.